L’étude des trajectoires professionnelles, une contribution à l’histoire de l’urbanisme. Le cas d’Étienne de Groër (1882-1952) - Angelo Bertoni (Mélanges de la Casa de Velázquez, 2024)
The professional trajectory of Étienne de Groër provides the opportunity to follow the development of town planning theories in the inter-war period which was marked by the gradual affirmation of the regional scale and the strengthening of the combination of the urban plan and regulations. His career also reveals the difficulties and wanderings of the town planning profession, which in the 1930s was facing the still emerging public commission and the competition from other professions. In this context, the close collaboration with a renowned urban planner, Donat-Alfred Agache, and the international mobility played a key role in Étienne de Groër’s professional affirmation. Lisbon and other major Portuguese cities gave him the opportunity to implement and refine his town planning ideas, in which the concept of the garden city figured prominently.